KRIMINALISASI TERHADAP GURU PRA DAN PASCA YURISPRUDENSI MAHKAMAH AGUNG REPUBLIK INDONESIA TENTANG GURU TIDAK BISA DIPIDANA SAAT MENJALANKAN DAN MELAKUKAN TINDAKAN PENDISIPLINAN TERHADAP SISWA (Jurnal Hukum Mimbar Justitia, 2022)
In principle, the Supreme Court Jurisprudence provides the consequence that the actions of teachers who reprimand or punish their students in the context of applying discipline while still in the corridor of education cannot be criminalized. To realize this requires law enforcement efforts from starting to change the community's understanding of the teaching profession, the attitude of law enforcement officials who must be wiser in responding to public complaints related to teacher and student relations. Legal remedies are the last way by still having to treat teachers humanely by paying attention to aspects of their prefaces. The research method uses a juridical normative approach in the form of descriptive analysis. The data source used is primary data in the form of data processing of criminalization cases of teachers pre and post Supreme Court Jurisprudence (MA). Secondary data in the form of observing cases of criminalization of teachers while primary data in the form of legislation.Keywords: Teacher, Criminalization, Protection, Humane.